Development of Novel Isoindolone‐Based Compounds against Trypanosoma brucei rhodesiense. Issue 9 (23rd September 2021) - Silva, Daniel G.; Feijens, Pim‐Bart; Hendrickx, Rik; Matheeussen, An; Grey, Lucie; Caljon, Guy; Maes, Louis; Emery, Flavio S.; Junker, Anna
Abstract: This study identified the isoindolone ring as a scaffold for novel agents against Trypanosoma brucei rhodesiense and explored the structure‐activity relationships of various aromatic ring substitutions. The compounds were evaluated in an integrated in vitro screen. Eight compounds exhibited selective activity against T. b. rhodesiense (IC50 <2.2 μm ) with no detectable side activity against T. cruzi and Leishmania infantum . Compound 20 showed low nanomolar potency against T. b. rhodesiense (IC50 =40 nm ) and no toxicity against MRC‐5 and PMM cell lines and may be regarded as a new lead template for agents against T. b. rhodesiense . The isoindolone‐based compounds have the potential to progress into lead optimization in view of their highly selective in vitro potency, absence of cytotoxicity and acceptable metabolic stability. However, the solubility of the compounds represents a limiting factor that should be addressed to improve the physicochemical properties that are required to proceed further in the development of in vivo‐active derivatives. Abstract : Development, SAR studies and primary in vivo evaluation of novel isoindolone‐based agents against Trypanosomiasis‐induced HAT infections are presented. The most potent derivative displays selective potency for Trypanosoma brucei rhodesiense (IC50 =40 nm ), no detectable side activity against T. cruzi and Leishmania infantum, no cytotoxicity against MRC‐5 and PMM cell lines and high in vitro metabolic stability, making it a promising lead for further drug development.